Program Instructional Profile (PIP): A User-Friendly Tool to Support Program Development and Implementation for Extension Professionals - Leman, Amy; Mott, Rebecca; Tummons, John (Journal of extension, 2024)
Not all Extension professionals enter the workplace with knowledge and experience in program development. Some may possess extensive expertise in their subject matter but need additional training in teaching-related competencies for adult or youth audiences. Even educators with extensive skill and experience benefit from thoughtful and intentional program planning and implementation design. This article describes the Program Instructional Profile (PIP), created for Extension professionals to design and outline the program delivery processes. We explain how to use the PIP and provide insight into the benefits and challenges of the uses for program development and implementation purposes.